Hubungan Tingkat Pengetahuan Suami dengan Rendahnya Penggunaan Alat Kontrasepsi Dalam Rahim (AKDR) di Desa Rebo, Kabupaten Bangka - Wulan Wijaya Wulan; Tetty Oktavia Limbong (PROFESSIONAL HEALTH JOURNAL, 2024)
Background: The IUD (Intrauterine Contraceptive Device) is a small object made of flexible plastic, has a copper coil or also contains hormones and is inserted into the uterus through the vagina and has threads. Highly effective, 0.5-1 pregnancies per 100 women during the first year of use. The low use of contraceptives in couples of childbearing age can have an impact on population growth which increases every year. Methods: This research is a cross-sectional study with random sampling technique. Results: The results of this study are that there is a relationship between the husband's level of knowledge and the low use of the IUD in Rebo Village with a p-value = 0.015. Conclusion: Based on the results of the study it can be concluded that there is a relationship between the knowledge level of the husband and the low use of the IUD. There were 48 (59.%) respondents who had good knowledge and used the IUD. Keywords: Contraception, IUD, Knowledge